2021
DOI: 10.1080/17441692.2020.1869800
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis of outdoor tobacco advertisement around children and adolescents in Indonesia

Abstract: designed the study, conducted data collector training, designed data architecture, conducted data cleaning and analysis, and prepared the manuscript. Desak Made Sintha Kurnia Dewi helped design the study, conducted training, data analysis and revised the manuscript. Septa Indra Puspikawati and Erni Astutik helped design the study, conducted training, coordinated field data collection, conducted data cleaning, and revised the manuscript. Soenarnatalina Melaniani helped design the study and revised the manuscrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Also in Surabaya the hotspots were located in areas where many lodgings and rental rooms were available. Evidence from this study show that adolescents are likely targeted by the tobacco industry, as indicated by high density of cigarette retailers [14][15][16] and high density of outdoor tobacco advertisements 13,23 around children and adolescent facilities especially in rural area. The high density of tobacco retailers can give adolescents the perception of wide availability of cigarettes 24 and the easy access to obtain cigarettes which may stimulate tobacco use among adolescents.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Also in Surabaya the hotspots were located in areas where many lodgings and rental rooms were available. Evidence from this study show that adolescents are likely targeted by the tobacco industry, as indicated by high density of cigarette retailers [14][15][16] and high density of outdoor tobacco advertisements 13,23 around children and adolescent facilities especially in rural area. The high density of tobacco retailers can give adolescents the perception of wide availability of cigarettes 24 and the easy access to obtain cigarettes which may stimulate tobacco use among adolescents.…”
Section: Discussionmentioning
confidence: 86%
“…We also conducted hotspot analysis using Getis-Ord Gi* to identify grids with significantly higher number of cigarette retailers with 5% and 1% significance level, a method that has been used in other studies. 13,17,20…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the KoboToolBox application was based on Google Maps, we used Google Sheets and geocoding add-ons to convert each facility address into geocodes (latitude and longitude). This technique has been well documented in the literature ( 16 18 ).…”
Section: Methodsmentioning
confidence: 98%
“…Our 2019 mapping (methods detailed elsewhere 16 ) revealed that stores placed retailer programme signs along with their store name at the front of their stores. There were 41 retailers that placed SRC signs and 11 retailers that placed GGSP signs.…”
Section: Methodsmentioning
confidence: 99%